Physico-chemical assessment of sediments of Tamarindo estuary and its tributaries, Guanacaste, Costa Rica - Bravo Chaves, Francela María (2012)
Sediments of Tamarindo estuary and its tributaries were evaluated in order to determine the effect of anthropogenic activities of the surrounding communities. The evaluation relied on texture, total phosphorus, organic matter, and heavy metal (Pb, Cu, Ni and Cr) analyses. The study spanned four sampling campaigns between October 2007 and April 2008, including four climatic seasons: rainy season, rainy-dry transition, dry season and dryrainy transition. Five sampling points were selected at Tamarindo estuary and three additional sites were set at Matapalo, Lomas and Lajas rivers. Ontario Ministry of the Environment regulation was used to evaluate sediment quality. It was determined that theanthropogenic activities of the surrounding communities exert a negative impact over the sediment quality; the pollution effect caused by such activities was rated as lower effect.